Blockchain Letter of Credit: Apakah Sekarang Saatnya? - Ruslan, Zuhri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Blockchain Letter of Credit (LC) is cutting-edge technology in international trade. It opens many opportunities to eliminate the deficiencies of current LC aspects. The research aims to answer how blockchain technology disrupts the LC workflow and whether now is the best time to adopt the blockchain LC. This research employed a narrative review approach. The result revealed that out of 226 articles from ScienceDirect, IEEE Xplore, Springer Open, Emerald insight, Research Gate, and Google Scholar, 26 articles were found to be relevant to answer the research questions. Significant findings from the research are that blockchain LC and smart contracts disrupt the LC workflow to become more efficient, secure from fraud and alterations, lower cost, and provide better visibility. Another finding is that adopting the technology is relevant provided that the cost to adopt has become affordable and when many banks and companies have adopted the blockchain LC. The process of adoption should be gradual.